Comparison between Different Techniques for Determining Hematological Parameters in Dogs (Global Journal of Medical Research, 2020)
The objective was to compare the hematological parameters obtained using automated, manual and estimated evaluation techniques, in order to verify whether these techniques can be used with confidence in dogs. Samples from 297 dogs were submitted to automated, manual and estimated blood count based on the hematocrit leveus and platelet estimation. Fisher's Exact Test, sensitivity, specificity calculations, positive predictive value, negative predictive value and kappa agreement coefficient (k) (p
Keywords: canine; hematological counter; hemogram